Analisis Pemahaman Mahasiswa Terhadap Penggunaan Website Lumi Education - Moch Fauzi; Lukman Jakfar Shodiq; Fahmi Abdul Halim (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2026)
This study aims to analyze students’ understanding of the use of the Lumi Education website in a Mathematics Learning Media course. A descriptive qualitative approach was employed involving mathematics education students who had used Lumi Education during the course. Data were collected through semi-structured interviews, classroom observations, and document analysis, and were analyzed thematically. The findings indicate that students have a fairly good understanding of the technical use of Lumi Education; however, its application in mathematics learning is still mainly limited to content presentation and simple practice activities. The integration of technology with pedagogy and mathematical content has not yet been fully optimized. These results highlight the need to strengthen instructional design that emphasizes pedagogical integration of technology to support more meaningful mathematics learning. Keywords: Student Understanding, Education Lumi Website